Mode of action of a non-pathogenic Fusarium oxysporum strain against Verticillium dahliae using Real Time QPCR analysis and biomarker transformation - Tjamos, Sotirios E.; Stringlis, Ioannis A.; Pantelides, Iakovos S (My University, 2009)
Verticillium wilt is a devastating disease of a wide range of herbaceous and woody plant hosts. It is incited by the soilborne fungus Verticillium dahliae. Management strategies are mainly focused on preventive measures. In a previous study, the efficacy of a non-pathogenic Fusarium oxysporum strain, designated as F2, isolated from a suppressive compost amendment, has been reported to reduce Verticillium wilt symptom development in eggplants under greenhouse and field conditions; in addition, antibiosis or parasitism were ruled out by using a dual culture test. In the present study, we investigated the mode of action of F2 against V. dahliae. For this purpose, the F2 and V. dahliae strains were transformed with the EGFP and DsRed2 reporter genes respectively, so as to visualize their presence on the root surface of eggplants. In addition, the ramification of both fungi into the plant vascular system was monitored by Real Time QPCR analysis. It was shown that F2 colonizes the root surface along the intercellular junctions excluding V. dahliae from the same ecological niche. In parallel, QPCR analysis showed that application of F2 reduces the levels of V. dahliae vascular colonization along with the disease severity. In a split root experiment it was demonstrated that F2 does not trigger the defense mechanisms of eggplants against V. dahliae. Therefore, it seems that competition for space or nutrients on the root surface are the main mechanism of action of F2 against V. dahliae
Keywords: Biological control; DsRed2; EGFP; Vascular wilts